PENGARUH KUALITAS PRODUK DAN PENATAAN BARANG TERHADAP MINAT PEMBELIAN ULANG PADA INDOMARET TALANG BANYU TEBING TINGGI - Kasinem Kasinem (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
This study aims to determine how the influence of product quality and product arrangement on repurchase interest at Indomaret Talang Banyu Tebing Tinggi. The sample in this study were 70 respondents who were consumers of Indomaret Talang Banyu Tebing Tinggi. The sampling method used by the researcher is Insidental sampling. This type of research is quantitative research using multiple linear regression and produce a regression equation : Y = 2.285+0.427+0.647. The results in this study are 1) The independent variable of product quality on the dependent variable of repurchase intention at Indomaret has a significant positive effect, because the value of T count is greater than T table and a significant level of 0.05 can be declared to have a positive effect. 2) The independent variable of goods arrangement on the variable of repurchase interest has a significant positive effect, because the value of T count is greater than T table and a significant level of 0.05 can be declared to have a positive effect. 3) Based on the F-Test, product quality and product arrangement have a positive and significant effect simultaneously on repurchase intention. It can be seen from the F-test that F count is 126,227, then Fcount > Ftable (44.404>2.74), with a significance of 0.000 < 0.05.